Students' Preferential Helpers in Facing Specific Areas of Concerns: An Indonesian Study - Setiawan, Jenny Lukito (Faculty of Psychology, Universitas Surabaya, 2009)
This paper describes a study designed to investigate preferred helpers in specific areas of concern among Indonesian students. A questionnaire consisting of 14 areas of concern and 14 choices of helpers was distributed to 1,279 students. Findings showed that Friend was consistently the most frequently selected helper in the areas of Academic, Transitions, Romantic Relationships, Other Relationships, Loss, Depression, and Anxiety. In the areas of Welfare, Parental Relationships, and Physical Health, Mother was the most common choice. In the problems related to Self, Compul- sive Behavior, Abuse, and Sexual Issues, students relied on their own resources. The study con- firms that the selection of helpers is influenced by the nature of problem. Makalah ini membahas penelitian yang dirancang untuk menyelidiki penolong yang lebih disukai membantu mengatasi permasalahan tertentu pada mahasiswa Indonesia. Sebuah kuesioner berisi 14 permasalahan dan 14 pilihan penolong, dibagikan kepada 1.279 mahasiswa. Hasilnya menun- jukkan bahwa Teman merupakan pilihan penolong yang paling sering dipilih dalam bidang Aka- demis, Transisi, Hubungan Romantik, Hubungan Lain, Kehilangan, Depresi, dan Kecemasan. Pa- da bidang Kesejahteraan, Hubungan Orang Tua, dan Kesehatan Fisik, Ibu merupakan pilihan yang paling umum. Permasalahan yang berkaitan dengan Diri, Perilaku Kompulsif, Pelecehan, dan Per- soalan Seksual, mahasiswa mengandalkan sumber daya mereka sendiri. Penelitian ini menegaskan bahwa pemilihan penolong dipengaruhi oleh sifat dasar permasalahan